Response of subaerial biofilms growing on stone-built cultural heritage to changing water regime and CO2 conditions. (March 2020) - Prieto, B.; Vázquez-Nion, D.; Fuentes, E.; Durán-Román, A.G.
Abstract: Like all objects exposed to the atmosphere, cultural heritage monuments and buildings must face the effects of global change. Some of environmental factors that are predicted to change and that are likely to affect the development of subaerial biofilms include water regime and CO2 concentration. This study investigated, for the first time, the influence of simultaneous environmental stressors on the development of subaerial biofilms on granite, the most commonly used stone in historical and modern buildings in Galicia (north-western Spain). Laboratory experiments revealed counteractive effects of water availability and increased CO2 concentration on the development of biofilms. Moreover, although the amount of colonizing biomass is not expected to change under the climate change projections for Galicia, the composition of the biofilm will probably change and cause more intense biodeterioration of stone cultural heritage. The study findings will be useful to help develop conservation and prevention policies against the deterioration of the built cultural heritage. Highlights: Climate Change affects the development of biofilms growing on Cultural Heritage. Biofilm growth is modified by water availability and CO2 atmospheric levels. CO2 effect seems to be limited by the availability of water.